Pregnancy Management System (MaternityMate) - Anuar, Nurul Nadia Husna; Ibrahim, Noraini (Applied Information Technology And Computer Science, 2025)
The Pregnancy Management System (MaternityMate) is an online platform designed to streamline and enhance the management of health information for pregnant women, including medical history, baby development and appointments. It addresses inefficiencies in the current manual system, including inconsistent procedures, delayed record-keeping, and limited appointment flexibility. The MaternityMate utilising the Prototyping Model which encompasses six phases: requirement gathering and analysis, design, prototyping, user evaluation and refinement, final product development, and testing and implementation. Every stage was modified to manage confidential data while addressing Klinik Kesihatan Batu 14 Hulu Langat's specific requirements. The system integrates features such as appointment scheduling, health monitoring, aiming to enhance communication between healthcare providers and patients, simplify administrative tasks, and improve data accuracy. The implementation of this system may help the clinic enhance maternal healthcare services by resolving ineffectiveness in the current manual approach, reducing delays and create a more effective procedure for doctors and nurses.